Nesmeyanova S.E. Levels (centers) of public authority: modern interpretation of theory and practice - A. V. Bleshchik; A. G. Kalinina; S. E. Nesmeyanova (Правоприменение, 2024)
The subject of the study is the legal relations arising from the public authority’s organization and its levels’ interaction after the constitutional reform of 2020. The organized interaction of the public authority levels determines the effectiveness of this system itself. Nowadays the issue of coordinated interaction between levels (centers) of public authority has become important, especially considering new global challenges in the different spheres. Therefore, the public authority and its levels as well as its organization and interaction become the subject of the legal theory and serve as a catalyst for legal changes, including constitutional one.The purpose of this paper is to examine the concept of public authority and analyze different approaches to the levels of it in theory and practice, paying the attention to the municipal level and its twofold role.Methodology. Formal-logical, comparative-legal, analysis methods were used. The interaction of levels of public authority is considered from the point of view of dialogism. This approach allows to establish that the interaction between levels of the public authority can be regarded as full only if they are organizationally isolated and financial and decision-making independent.Main results. The authors demonstrate the vitality of the theory that predetermined the ongoing changes in the Russian legal system, and examine approaches to the concept of public authority and its levels. It is however apparent that the created system does not include the level of community public authority. Based on the analysis of decisions of the Constitutional Court of the Russian Federation, the evolution of levels of public authority in their interaction with each other is revealed. Besides, certain elements of centralization of public administration are essentially opposed to the principle of subsidiarity, the analysis of which is also presented in the paper since it determines the scope of competence of public legal entities and allows achieving maximum freedom and efficiency of the activities of bodies. At last, the authors give characteristics to the municipal level by two opposing trends: globalization and glocalization.Conclusions. In Russia the practice of organizing public authority does not fully comply with the principle of subsidiarity as well as the new legal term of the system of public authority does not include all the variety of elements that the constitutional scientists mentioned, including the community public authority. This one along with the municipal authority level assessed as a potential matter for further reforms necessary for the formation of a trust of public authorities and for the population’s participation in state affairs.